Lateral transfer of a phytopathogenic symbiont among native and exotic ambrosia beetles. (10th May 2013) - Carrillo, D.; Duncan, R. E.; Ploetz, J. N.; Campbell, A. F.; Ploetz, R. C.; Peña, J. E.
<x xml:space="preserve">Abstract</x> Different ambrosia beetle species can coexist in tree trunks, where their immature stages feed upon symbiotic fungi. Although most ambrosia beetles are not primary pests and their fungal symbionts are not pathogenic to the host tree, exceptional situations exist. Notably, Xyleborus glabratus carries a phytopathogenic symbiont, Raffaelea lauricola, which causes laurel wilt, a lethal disease of some Lauraceae species. Both X. glabratus and R. lauricola are natives of Asia that recently invaded much of the coastal plain of the southeastern USA. This study examined ambrosia beetles that breed in susceptible trees in Florida (USA), including avocado (Persea americana), redbay (P. borbonia) and swampbay (P. palustris). Raffaelea lauricola was recovered from six of eight ambrosia beetle species that emerged from laurel wilt‐affected swampbay trees, in addition to X. glabratus. Controlled infestations with cohorts of the six species other than X. glabratus revealed that each could transmit the pathogen to healthy redbay trees and two could transmit the pathogen to healthy avocado trees; laurel wilt developed in five and one of the respective beetle × host interactions. These results indicate flexibility in the lateral transfer of a non‐native ambrosial fungus to other ambrosia beetles, and for the first time documents the transmission of a laterally transferred phytopathogenic symbiont by new ambrosia beetle species. Additional work is needed to determine whether, or to what extent, the new beetle × R. lauricola combinations play a role in spreading laurel wilt.